Investigating AI Usage in English Language Learning: Frequency, Preferences, and Perceived Effectiveness on Speaking and Writing Skills - Jeffri Dian Andika; Karelina Natalya Andreevna; Rozanah Katrina Herda; Elina S Savitskaya; Fani Nabila Titania; Elizaveta Ivashova (Wahana Pendidikan, 2025)
Inspired by the different usage patterns, preferences, and perceived effectiveness of AI tools to support English productive skills, the study provides their comparative analysis among students in Indonesia and Russia. The study used a mixed-methods approach with a convergent parallel design to conduct the research.  While the researcher employed online questionnaires containing ordinal scales using Likert-type items to collect quantitative data, interviews with open-ended questions were used to get qualitative data. There are 175 students from each country as the research sample. The study results confirm that Russian students access AI weekly or monthly, and Indonesian students use AI tools daily. Students in both countries admit that chatbots and language learning apps are their preferred AI tools. In terms of perceptions, while Indonesian students consider AI a beneficial tool to support their writing, Russian students classify AI tools as a valuable companion in speaking. They also stated their neutrality due to excessive accuracy and dependency. To develop AI tools, students highlighted the essence of more tailored, interactive, and attainable features. In conclusion, although AI tools support English productive skills, there is a need to incorporate pedagogical guidance and ethical considerations in their implementation.